2018
DOI: 10.1016/j.amepre.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Physical Activity Opportunities: Results From a Community-Based Family Child Care Intervention

Abstract: This article is part of a supplement entitled Building Thriving Communities Through Comprehensive Community Health Initiatives, which is sponsored by Kaiser Permanente, Community Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…NCAL strategy-level evaluation results included in other papers in this issue showed mixed findings for corner store strategies 26 and more positive results in early childhood settings. 25 Modest positive results were found for population changes from the youth and adult surveys across the entire initiative (data not shown). Of the 92 pre and post comparisons (Note: one community in SCAL did not do the school surveys, so there were 44 comparisons in SCAL, not 48), just over one fifth (n¼20, 22%) were positive-either statistically significant (po0.05, n¼11) or trending (po0.10, n¼9)-and 7 (8%) were negative and significant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…NCAL strategy-level evaluation results included in other papers in this issue showed mixed findings for corner store strategies 26 and more positive results in early childhood settings. 25 Modest positive results were found for population changes from the youth and adult surveys across the entire initiative (data not shown). Of the 92 pre and post comparisons (Note: one community in SCAL did not do the school surveys, so there were 44 comparisons in SCAL, not 48), just over one fifth (n¼20, 22%) were positive-either statistically significant (po0.05, n¼11) or trending (po0.10, n¼9)-and 7 (8%) were negative and significant.…”
Section: Discussionmentioning
confidence: 94%
“…NCAL strategy-level evaluation results in corner stores and early childhood settings are presented in separate papers in this issue. 25,26…”
Section: Methodsmentioning
confidence: 99%
“…Differences were found between FDC service providers trained or not trained in Munch & Move regarding professional development and nutrition, physical activity and screen time policies but not in the resources provided. Other studies have generally found that professional development has improved both policies and resources [11][12][13] , however a recent US study, which focused on educator professional development, found no difference in nutrition, physical activity or screen time policies between intervention and control. 14…”
Section: Discussionmentioning
confidence: 95%
“…Although studies may have examined interventions to improve family day care environments, not having a parallel control group resulted in their exclusion. Online Appendix B provides an overview of such types of previous interventions undertaken in this setting (29)(30)(31)(32)(33)(34)(35)(36) .…”
Section: Study Selectionmentioning
confidence: 99%